Representasi Budaya Patriarki yang Dialami Perempuan dalam Film Yuni Karya Kamila Andini - Sazali, Hasan; Alfanny, Aulia; Pratama, Rabiulza (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study create is to analyze the representation of patriarchal culture in the Yuni film. This study uses a qualitative approach with a semiotic approach. Data collection techniques used documentation and observation. Data collection done by collecting scenes in the film Yuni that represent patriarchal culture. The data analysis technique used John Fiske semiotics consists of three levels: the level of reality, representation, and ideology. The result of the research show that the Yuni film represents patriarchal culture. The analysis in this study carried out by paying attention to conversations, facial expressions, the environment, the cinematography used in the scenes in the Yuni film. There are findings of patriarchal culture shown in the Yuni film, namely: a complete division of labor for women and the double burden received by women, restrictions on the movement of women in terms of pursuing higher education, sexual exploitation of women, physical violence perpetrated by men against women, and restrictions on the movement of women by educational institutions. Suggestions from this study are still short comings in it, therefore there is a need for further in-depth research and developing topics related to the concept of gender presented in the film titled Yuni, the interpretations generated by the researchers in this study can be different. Further research is needed, and the community is expecting to be able to absorb films as a medium for community learning that gender inequality is still common in society.